75P Immune-related toxicities in NSCLC: Real-world experience from a tertiary cancer center. (15th December 2019) - d'Arienzo, P D; Olsson-Brown, A C; Sallam, M; Ortega-Franco, A; Wong, H; Escriu, C
Abstract: Background: Immune checkpoint inhibitors (ICIs) are key in the treatment of advanced non-small cell lung cancer (NSCLC). However, there is a paucity of large real-world case series on timing and severity of immune-related adverse events (irAEs) that could inform treatment service provision. Methods: A retrospective study of patients with advanced NSCLC treated with ICIs at The Clatterbridge Cancer Centre between 2016 and 2018 was conducted to review irAEs in the context of therapeutic efficacy. Kaplan Meier analysis, Mann-Whitney and chi-squared tests were used. Results: 303 patients were identified. Median age was 68 years; 83 patients (27%) had a performance status (PS) of 0; 85 (28%) had an ACE-27 comorbidity score ≥2. 277 (91%) had pembrolizumab (107 (35%) first line), 21 (7%) nivolumab and 5 (2%) atezolizumab. Median number of cycles was 6 (range 1-29). Median progression-free and overall survival (PFS/OS) were 5.0 and 10.0 months. IrAEs were reported in 40% of patients and 13% experienced multiple irAEs; 11% were ≥G3. The most common irAEs were dermatitis (12%), dysthyroidism (9%), colitis (6%), hepatitis (5%), arthralgia (5%), pneumonitis (5%); the most common ≥G3 irAEs were pneumonitis (3%), hepatitis (2%) and colitis (2%). Treatment was discontinued due to irAEs in 12% of patients. Median time to irAEs onset by system involved varied between 46 days (hyperthyroidism) and 122 days (arthralgia). There was no association between irAEs and age (p = 0.16), PS (p = 0.46), or ACE-27 score (p = 0.68). 83% of irAEs occurred within 6 months of initiating ICIs; no clear correlation between irAEs incidence and time on treatment was found. Patients with irAEs within 6 months of treatment had longer PFS (7.1 vs. 3.9 months, HR 0.70, p = 0.014) and OS (15.6 vs. 7.7 months, HR 0.48, p < 0.001) than those without irAEs. Notably, patients experiencing irAEs ≥G2 within the first 21 days of treatment had poorer clinical outcomes than those with later irAEs (median PFS 2.9 vs 10.3 months, p < 0.001; median OS 5.9 vs. 20.3 months, p = 0.001). Conclusion: In our large real-world retrospective cohort study the incidence of irAEs reflected that seen in clinical trials. There appears to be a toxicity-efficacy relationship with irAEs; however, larger studies are required to validate this. Legal entity responsible for the study: The Clatterbridge Cancer Centre NHS Foundation Trust. Funding: Has not received any funding. Disclosure: A.C. Olsson-Brown: Honoraria (self): MSD; Honoraria (self), Research grant / Funding (self): Roche; Honoraria (self), Advisory / Consultancy: Bristol-Myers Squibb; Research grant / Funding (self): Eli Lily; Research grant / Funding (self): Novartis. C. Escriu: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): AstraZeneca; Advisory / Consultancy: MSD; Speaker Bureau / Expert testimony: Bristol-Myers Squibb; Advisory / Consultancy, Research grant / Funding (self): Boeringher Ingelheim; Speaker Bureau / Expert testimony: Pfizer. All other authors have declared no conflicts of interest.